The Influence Of Market Sentiment On Investment Decisions On The Indonesian Stock Exchange Decisions On The Indonesian Stock Exchange The Influence Of Market Sentiment On Investment - Santika, Lara; Susena , Karona Cahya (Universitas Dehasen Bengkulu, 2025)
This research aims to evaluate the influence of market sentiment on investment decisions on the Indonesia Stock Exchange (IDX). Market sentiment is understood as the collective perception of investors that can influence investment behavior, using both fundamental and technical approaches. This study employs a quantitative approach using a survey of active investors on the IDX. The results demonstrate a positive and significant influence between market sentiment and investment decisions. Positive market sentiment tends to encourage investors to make more rational decisions. Furthermore, the ability to conduct fundamental and technical analysis was found to strengthen the relationship between market sentiment and investment decision-making. This research emphasizes the importance of investor understanding of market sentiment dynamics in the context of making more accurate and strategic investment decisions.